A case study on quality of services for bus performance in Putrajaya, Malaysia - Norhisham, Shuhairy; Ismail, Amiruddin; Borhan, Muhamad Nazri; Katman, Herda Yati; Khalid, Nor Hazwani Nor; Zaini, Nur'atiah (International Journal of Engineering and Technology, 2018)
In accessing quality bus service in Putrajaya, 6 attributes were chosen as suggested by experts and summary review of four guidelines in bus transit manual from New Zealand, United Kingdom, United State and Australia. Six (6) attributes was identified, namely Services Hours, Load Factor for passenger, Comparison Car and Bus Travel , Frequency of Bus, on-time Performance and Coverage Services Area was conducted to check the quality of services for bus in Putrajaya. As a finding hours of services, passenger load factor and transit auto-motive comparison travel time was good with A and B rating of quality of services. Meanwhile, service coverage area and on time perfor-mance was factor needed to improve immediately. Overall it was found that the bus services in Putrajaya, according to the accessing method by Transit Capacity and Quality of Service Manual (TCQSM), was considered as moderate.